Supervisors’ Perspectives on Generic Difficulties Faced by EFL Students in Writing Thesis: A Multiple Case Analysis - Tiwari, Hari Prasad (Molung Educational Frontier, 2023)
Writing a thesis is one form of academic writing that requires adequate research-related knowledge, interest, motivation, and effort. For this reason, students often consider thesis writing a challenging task. This qualitative multiple case study seeks to explore supervisors’ perspectives on the difficulties faced by master’s level English as a Foreign Language (EFL) students while writing theses in English Education. The participants consisted of eight thesis supervisors who have supervised at least ten master’s theses written by the students who studied English Education as the specialization subject at the Master’s level at constituent campuses under the Faculty of Education (FoE), Tribhuvan University (TU). I used simple random sampling to select the constituent campuses and purposive sampling to select the sample. I collected the data using a semi-structured interview. The interviews were conducted via a video conferencing tool named Zoom. According to the interest of the participants, the interviews were conducted in English, and all the interviews were audio-video recorded in Zoom. Recorded interviews were then transcribed and analyzed using the constant comparison method of qualitative data analysis. The findings show that the students’ typical challenges with thesis writing were connected to their difficulty in integrating and generalizing related literature, their inability to prepare a theoretical framework, their lack of general knowledge of research, their lack of knowledge of citation and referencing, their difficulties in selecting appropriate methodology, and their inability to use academic language. The study concluded that EFL graduate students, regardless of their performance on the written examinations, depend substantially on their supervisors when writing a thesis.